Proyecto de factibilidad para la implementación de una empresa industrial de vinos cítricos y su comercialización en la provincia de Loja. - Vivanco, Narcisa Jacqueline (2012)
The investigation work refers to the implementation of an industrial company of citric wines and its commercialization in the county of Loja, for the depreciation of the production costs, since in the cantons of Chaguarpamba, Puyango, Avocados Catamayo, among other, the matter exists it prevails required and in the city of Loja, the necessary manpower. To determine the feasibility of the project, he/she was carried out the corresponding market study, size and localization, engineering of the project, financial evaluation and the organization of the company. In the market study you could determine that an effective demand exists for the first year of activity of the company of 406.168 flasks of 750 ml., enough to implement the industrial plant in the city of Loja. After having carried out the financial evaluation, with their respective indexes, as the Current Net Value with a value of 95035.77 dollars, an Internal Rate of Return of the one 60.34%, the Relationship Benefits Cost of 1.15, the Period of Recovery of Capital 6 years old, 7 months and 24 days, they give positive indicators as a result, which assure us that it can be carried out this project without more difficulties. One of the financial indicators that demonstrate that the project is profitable is TIR that gives us a much higher percentage that the opportunity cost that has capital in the local market, for such a reason makes sure that the project is executable. Their legal and administrative organization has also settled down with an artificial identification of Company in Collective Name, likewise he/she settled down the hierarchical different levels and with the functions that it should carry out each one of people that you/they will lend services in the company. This as such, it is structured and it has been foreseen that the lifespan of the project is of a ten year-old period, being located in the city and county of Loja.